Toward Sustainable Development: Energy Transition Scenarios for Oil-Dependent Countries, with Iran as a Case Study - Bahareh Heidary; Mohammad Ali Kiani; Farzin Golzar (Energies)
Oil-dependent countries face persistent challenges, such as energy supply–demand imbalances, overreliance on fossil fuels, declining economic diversification, and environmental degradation. In response, policymakers are increasingly advocating for comprehensive energy transitions to enhance energy and environmental security while promoting sustainable development. This study evaluates Iran’s energy transition through the modeling of five scenarios using the EnergyPLAN software V16.3. These scenarios, ranging from increased fossil fuel production to renewable energy deployment, subsidy reform, and energy efficiency, were developed based on a systematic literature review and expert interviews. Key indicators such as carbon emissions, primary energy demand, and supply–demand balance were used to assess the long-term impacts of each scenario through 2040. The Transition Scenario Policy (TSP), which integrates elements of all other scenarios, emerged as the most effective pathway for reducing emissions, correcting supply–demand imbalances, and aligning with sustainable development goals. The novelty of this study lies in its mixed-method approach, combining qualitative stakeholder insights with quantitative modeling, offering a replicable framework for energy transition planning in similar oil-dependent contexts. The practical implications support evidence-based policy making, while the results open avenues for future research on adaptive energy governance, policy trade-offs, and resilience under global uncertainty.